Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-16T07:19:41+01:00
Bonjour,

1) -9x+6x²-9+12x-4x² =
     2x²+3x-9

2) (3-2x)(-3x-3+2x) =
   (3-2x)(-3-x)

3) 2(x²+6x/4+9/16)-81/8 =
   2x²+12x/4+18/16-81/8 =
   2x²+24x/8+9/8-81/8 =
  2x²+3x-9
  • Utilisateur Brainly
2014-03-16T07:38:31+01:00
Exercice 1:

1) Développement:

f(x) = -3x (3-2x) - (3-2x)²
f(x) = -9x + 6x² - (9 - 12x +4x²)
f(x) = -9x + 6x² - 9 +12x - 4x²
f(x) = 2x² + 3x -9

2) Factorisation:

f(x) = -3x (3-2x) - (3-2x)²
f(x) = (3-2x) (-3x -3 +2x)
f(x) = (3-2x) (-x-3)

3) Vérification:
 
Soit A=  2 (x+3/4)² - 81/8

A= 2 (x² + 3/2x + 9/16) - 81/8
A= 2x² + 3x + 18/16 - 81/8
A= 2x² + 3x + 9/8 - 81/8
A= 2x² + 3x - 72/8
A= 2x² + 3x -9

On remarque que A est égal à la forme développée de la fonction f donc: f(x) = 2 (x+3/4)² -81/8.